Software para ejercitar la memoria SEMALZ Plus (2017)
Alzheimer's syndrome is a degenerative disease that acts directly on the connections of the cells of the brain, also reducing the muscular mass of the same. This is constituted in different stages that go from the loss of the capacity to form new memories until the capacity of an effective regulation of the respiration and of the cardiac pulse leading to the death. Currently there are different treatments to decrease the rate of degenerative activity of this syndrome classified in pharmacological and non-pharmacological. In order to support the development of non-pharmacological treatments through mobile applications for this disorder, a software was developed under the GameMakerStudio tool, which implemented a series of 7 (seven) exercises able to combat the degenerative development of the illness. Different field tests were performed on Alzheimer's Day Club Neuroactive patients, which led to changes required to make the application friendlier to the end user.